Blutungsrisiko und Blutungsnotfälle unter Rivaroxaban - Koscielny, J.; Beyer-Westendorf, J.; von Heymann, C.; Braun, J.; Klamroth, R.; Lindhoff-Last, E.; Tiede, A.; Spannagl, M. (Hämostaseologie, 2012)
Rivaroxaban, the first direct factor-Xa inhibitor anticoagulant, has been approved for the prevention of venous thromboembolism in adult patients undergoing elective hip or knee replacement surgery, for stroke prophylaxis in patients with non-valvular atrial fibrillation and for the treatment of deep vein thrombosis. There is no requirement for coagulation monitoring with rivaroxaban in routine clinical practice. However, in certain clinical circumstances such as life-threatening bleeding or an emergency operation the measurement of the thromboplastin time with a sensitive reagent will deliver first information. A quantitative determination of rivaroxaban plasma concentration is possible using an anti-factor Xa assay.In the case of a patient under long-term anticoagulation with rivaroxaban requiring an elective surgery, a discontinuation of rivaroxaban 20 to 30 hours before the operation is sufficient to normalize the associated bleeding risk, as long as the renal and liver function is normal. A longer interval should be taken into consideration, when the patient presents a renal and liver impairment or is of a higher age. In the event of an emergency operation effective rivaroxaban concentrations might be present. Nevertheless, we advise against using a prophylactic dose of factor concentrates. Recommendations: From a clinical perspective, in the event of a minor bleeding we recommend a temporary discontinuation of rivaroxaban, whereas for clinically relevant major or severe bleeding events a mechanical compression or a limited surgical i. e. interventional treatment is required. Supportive measures such as the administration of blood products or tranexamic acid might be beneficial. In addition to haemodynamic supportive measures life threatening bleeding events demand a comprehensive haemostasis management, as well as the application of PCC.
Keywords: Rivaroxaban; anticoagulants; bleedings; bleeding risk; management of haemostasis; perinterventional management